“The impact of COVID-19 on employee productivity and the future of remote work” - Sultan Alenazi; Jagannath Mohanty; Maheswaran Srinivasan; Durga Prasad Samontaray (PLoS ONE, 2026)
Purpose This paper explores the impact of the COVID-19 pandemic on employee productivity and the future of remote work beyond the pandemic years. Using data collected from 646 remote workers, we examined the influence of interpersonal relations, time management, stress, and skill development on productivity. Design/methodology/approach We validated our model using structural equation modelling (SEM), and the results revealed that the sudden shift to remote work had no significant negative impact on productivity. Findings The results of this study may encourage HR managers to expand remote work opportunities, thereby enhancing talent attraction and retention in a highly competitive job market. Originality/value Despite prevalent concerns about COVID-19 and the evolving nature of workplaces, employees perceived remote work as offering greater flexibility in task organization and the opportunity to create a healthier work-life balance. Furthermore, our findings suggest that HR managers should consider allowing remote work post-pandemic as a strategic aspect of workplace evolution.